The Impact of Project Activities on the International Business Development - KUKHARUK, Anna; NAGIYEVA SADRADDIN, Ruhiyya; ANISIMOVYCH-SHEVCHUK, Olha; MARUKHLENKO, Oksana; KAPYRULYA, Mykhaylo (Theoretical and Practical Research in Economic Fields; Vol 15 No 3 (2024): TPREF, Volume XV, Issue 3(31), Fall 2024, 2024)
The impact of project activities on the international business development is an urgent issue in view of the increasing global expansion and intensifying competition between companies. The aim of the study is to assess the impact of project activities on the international business development. The research methodology is based on the analysis of modern trends in the development of international business using econometric modelling, statistical analysis, and extrapolation. The impact of project activities on business expansion was determined and the use of Agile and PMBOK methodologies was assessed. The obtained results show the experience of international companies in the use of project methodologies, which increased by 20% in 2023 compared to 2022. The study found that project activities have a significant impact on the international business development thanks to the support of bank lending. The results show that the effective use of project methodology optimize production processes and reduce costs in international business. The available results emphasize the importance of strategic project management for the successful development of enterprises on the international market using the example of Azerbaijan. The research findings indicate the effective practice of applying innovative technologies in project activities with the help of Agile for international business development. A comparative analysis of management approaches objectively determines the advantages, which include the promptness of decision-making, ensuring organizational efficiency. Further research into project management methods in international business will contribute to the improvement of management practices and the development of strategies that meet the modern globalization challenges.